2008
DOI: 10.1108/13590790810907254
|View full text |Cite
|
Sign up to set email alerts
|

The impact of internet crime on development

Abstract: Purpose -The global wave of information and communication technologies (ICT) development has become a strong driving force in almost every aspect of development. This paper aims to explore the impact of internet crime on individuals, organisations, businesses and government agencies in both developed and developing countries with special reference to developing countries. Design/methodology/approach -The analysis in this paper is based on extensive review of published research works, which provide theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…The second issue relates to the youthfulness of the perpetrators as well as their degree of technical savvy. Other studies have shown that offenders are more likely to share a broader range of social characteristics and are likely to be young, clever, often without prior criminal records, possessing expert knowledge and often motivated by a variety of financial and non-financial goals (Balkin et al, 2006;Coomson, 2006;Salifu, 2008;Wall, 2001). The third issue is that most cases go unreported due to lack of confidence in the prosecuting process and fear of embarrassment on the part of the victims.…”
Section: Relevant Literature On Cybersecurity In Ssamentioning
confidence: 97%
“…The second issue relates to the youthfulness of the perpetrators as well as their degree of technical savvy. Other studies have shown that offenders are more likely to share a broader range of social characteristics and are likely to be young, clever, often without prior criminal records, possessing expert knowledge and often motivated by a variety of financial and non-financial goals (Balkin et al, 2006;Coomson, 2006;Salifu, 2008;Wall, 2001). The third issue is that most cases go unreported due to lack of confidence in the prosecuting process and fear of embarrassment on the part of the victims.…”
Section: Relevant Literature On Cybersecurity In Ssamentioning
confidence: 97%
“…Pesatnya perkembangan teknologi dan akses terhadap informasi yang semakin mudah juga turut berperan dalam tindak kriminalitas. Adanya akses internet memengaruhi terjadinya tindak kekerasan seksual, perundungan (bullying), kekerasan SARA, pencurian informasi (Bhuller et al, 2013;Chan et al, 2013;Nolte, 2017;Reisig, et al, 2009;Salifu, 2008;Schechtman et al, 2006). Indikator 2002 2005 2012 2013 2014 2015 2016 2017 Growth PDB (%) 4,50 5,69 6,16 5,71 5,21 4,99 5, (Sasongko, 2019).…”
Section: Pendahuluanunclassified
“…The ambiguity surrounding the issue of what constitutes a crime has also resulted in the general absence of legislation and regulation governing activity in virtual worlds. The result has been the materialisation of various types of crime with real-life ramifications (Salifu, 2008). One category of crime relates to those committed within virtual environments involving theft or destruction of virtual property.…”
Section: Virtual Crimementioning
confidence: 99%